The Use of Principal Component and Cluster Analysis to Differentiate Banana Peel Flours Based on Their Starch and Dietary Fibre Components - Saifullah Ramli; Noryati Ismail; Abbas Fadhl Mubarek Alkarkhi; Azhar Mat Easa (Tropical Life Sciences Research, 2010)
Banana peel flour (BPF) prepared from green or ripe Cavendish and Dream banana fruits were assessed for their total starch (TS), digestible starch (DS), resistant starch (RS), total dietary fibre (TDF), soluble dietary fibre (SDF) and insoluble dietary fibre (IDF). Principal component analysis (PCA) identified that only 1 component was responsible for 93.74% of the total variance in the starch and dietary fibre components that differentiated ripe and green banana flours. Cluster analysis (CA) applied to similar data obtained two statistically significant clusters (green and ripe bananas) to indicate difference in behaviours according to the stages of ripeness based on starch and dietary fibre components. We concluded that the starch and dietary fibre components could be used to discriminate between flours prepared from peels obtained from fruits of different ripeness. The results were also suggestive of the potential of green and ripe BPF as functional ingredients in food. Tepung kulit pisang yang disediakan dari buah pisang Cavendish dan Dream (berangan) yang hijau dan masak telah dinilai jumlah kanji (TS), kanji hadam (DS), kanji rintang hadam (RS), jumlah serat dietari (TDF), serat dietari larut (SDF) dan serat dietari tak larut (IDF). Analisa komponen principal (PCA) menunjukkan hanya satu komponen yang bertanggungjawab untuk 93.74% daripada jumlah varian yang terdapat dalam komponen kanji dan serat dietari yang membezakan tepung pisang masak dan hijau. Analisa kluster (CA) dari data yang sama memperoleh dua kluster signifikan (pisang hijau dan masak) yang menunjukkan perbezaan perilaku mengikut tahap kematangan. Kesimpulannya, komponen kanji dan serat dietari boleh digunakan untuk mendiskriminasi antara tepung yang disediakan dari kulit buah yang berbeza tahap kematangannya. Keputusan juga menunjukkan potensi tepung kulit pisang hijau dan masak sebagai bahan berfungsi dalam makanan.